2018
DOI: 10.21608/zumj.2018.13268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Infection Control Program on Catheter Associated Urinary Tract Infection in Intensive Care Units at Zagazig University Hospital

Abstract: Background: Catheter-associated urinary tract infection produces substantial morbidity in hospitalized patients including discomfort, fever, malaise and unnecessary antibiotic use, which may become an important source of antibiotic resistant organisms. Further, the catheterized urinary tract acts as a reservoir for the dissemination of these drug resistant organisms to other patients. Aim of the study: was to improve the safety of intensive care unit (ICU) patients with urinary catheter via decreasing the inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
3
1
1
Order By: Relevance
“…This may be due to the study's inclusion criteria of the age group that ranged from 18 to 45 years old to ensure that the patients were free from infections and other age-related diseases. Similarly, Selim (2018) reported that the mean age of their patients was 37.3 ±11.4 which is congruent with our findings. On the Contrary, Abdel-Hakeim and Hamza (2018) revealed that the most common age group of the studied patients was between 40 and 50 years old with a statistically significant difference between the studied groups.…”
Section: Section I: Demographic Characteristics and Clinical Data Of ...supporting
confidence: 92%
See 2 more Smart Citations
“…This may be due to the study's inclusion criteria of the age group that ranged from 18 to 45 years old to ensure that the patients were free from infections and other age-related diseases. Similarly, Selim (2018) reported that the mean age of their patients was 37.3 ±11.4 which is congruent with our findings. On the Contrary, Abdel-Hakeim and Hamza (2018) revealed that the most common age group of the studied patients was between 40 and 50 years old with a statistically significant difference between the studied groups.…”
Section: Section I: Demographic Characteristics and Clinical Data Of ...supporting
confidence: 92%
“…This is because the study settings have some limitations such as the lack of some supplies, the high ratio of patients to nurses, and non-compliance of physicians and nurses with handwashing and gloving guidelines during UC insertion or care. In this regard, our findings are supported by several studies which were conducted in developing countries as Egyptian studies (Abdesalam, Ahmed, & Khalil, 2018;Ahmed & Shehata, 2020;Aly, Tawfeek, & Mohamed, 2016;Amine et al, 2014;Ismail et al, 2019;Selim et al, 2018;Talaat et al, 2010), Saudia studies (Abdel-Hakeim, & Hamza, 2018;Raslaan, 2012) and one Lebanese study (Kanj et al, 2013). These studies reported a high CAUTIs rate.…”
Section: Section Iii: Comparing the Cautis Rate Between The Studied G...supporting
confidence: 86%
See 1 more Smart Citation
“…The result of the present study revealed that the majority of nurses had adequate level toward CAUTI prevention. This finding is inconsistent with Sobeih and Nasr (2015), who stated that only 12.5% of the studied nurses had competent level of practices as regards urinary catheter care while this result contradicted with Selim et al (2018) 14 and Mukakamanzi (2017), who found that a high percentage of nurses has shown a good implementation of different practices towards catheter CAUTI prevention.…”
Section: Discussioncontrasting
confidence: 59%
“…This transition has resulted in a greater reliance on OEPs by both faculty and students, both inside and outside the classroom. It serves as a complementary approach to traditional learning methods, providing opportunities for interactive and engaging educational experiences (Schuler et al, 2021). As the nursing field embraces digital advancements, the use of webenhanced learning is expected to play a vital role in facilitating learning and preparing future nurses for their professional roles.…”
Section: Significant Of the Studymentioning
confidence: 99%